2013
DOI: 10.1136/annrheumdis-2013-204172
|View full text |Cite
|
Sign up to set email alerts
|

Key findings towards optimising adalimumab treatment: the concentration–effect curve

Abstract: Adalimumab trough levels in a range of 5-8 μg/mL are sufficient to reach adequate clinical response. These levels are influenced substantially by concomitant MTX use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
162
3
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(183 citation statements)
references
References 19 publications
14
162
3
4
Order By: Relevance
“…However, the pharmacokinetics of infliximab and adalimumab were found to be influenced by methotrexate co-medication, trough concentrations of both infliximab [65] and adalimumab [55] being higher in the presence of methotrexate. Methotrexate was associated with a 30 % decrease in infliximab clearance and an increase in t from 9.3 to 13.3 days [29].…”
Section: Influence Of Co-medicationsmentioning
confidence: 90%
See 2 more Smart Citations
“…However, the pharmacokinetics of infliximab and adalimumab were found to be influenced by methotrexate co-medication, trough concentrations of both infliximab [65] and adalimumab [55] being higher in the presence of methotrexate. Methotrexate was associated with a 30 % decrease in infliximab clearance and an increase in t from 9.3 to 13.3 days [29].…”
Section: Influence Of Co-medicationsmentioning
confidence: 90%
“…2). Of note, methotrexate co-treatment did not influence infliximab pharmacokinetics in ankylosing spondylitis patients, probably because antigen burden is lower in this disease than in RA [55]. No sound data reported an influence of other disease-modifying anti-rheumatic drugs (such as azathioprine or prednisolone) on mAbs pharmacokinetics [66].…”
Section: Influence Of Co-medicationsmentioning
confidence: 97%
See 1 more Smart Citation
“…The concentrations of anti-TNF biopharmaceuticals (infliximab, adalimumab) were shown to increase when methotrexate, an inhibitor of dihydrofolate reductase, is co-administered notably in RA patients [157] . Pharmacokinetic modelling studies of infliximab showed that immunomodulator (such as methotrexate) co-treatment is associated with lower infliximab clearance [105,111] , independently from CRP levels.…”
Section: Influence Of Concomitant Treatmentmentioning
confidence: 99%
“…Так, M. Pouw и соавт. [31] проанализиро-вали взаимосвязь эффективности АДА с уровнем препара-та в сыворотке у 221 пациента с РА. Авторами было проде-монстрировано, что клинический эффект АДА увеличива-ется при повышении концентрации препарата в сыворот-ке.…”
Section: Discussionunclassified